Working Paper 9: The situation of Financial Intelligence Units in Central and Eastern Europe and the former Soviet Union (Basel Institute on Governance Working Papers, 2011)
The transition process in many countries in Central and Eastern Europe from a one-party state to a democratic system has been long and difficult and has frequently been accompanied by institutional instability.The judiciary and law enforcement bodies have been no exception. Both have suffered from a weak legal tradition in many countries of the region, weak implementation of existing legislation, limited operational effectiveness, corruption and the influence of informal personal networks. These developments can also be observed in the area of financial intelligence.Following the fall of the Berlin wall in 1989 and the events of September 2001, most countries of the region adopted legislation aimed at combating money laundering and terrorist financing, as required by their international commitments as well as EU entry requirements. In this context, most countries also set up the required institutions, notably a Financial Intelligence Unit (FIU).
Keywords: anti-money laundering; AML/CFT; Financial Intelligence Unit; informal networks; anti-corruption legislation; Central Europe; Eastern Europe